Case Study: Chronic Recurrent Multifocal Osteomyelitis in the Femoral Diaphysis of a Young Female - Jeffrey S. Quon; Anne K. Dzus; David A. Leswick (Case Reports in Radiology)
Chronic recurrent multifocal osteomyelitis (CRMO) is relatively uncommon. Even though the name suggests it is the result of infection, this is not likely the case. Instead it is more likely the result of genetic, autoimmune, or autoinflammatory causes. Although CRMO has a benign course and responds well to anti-inflammatory medications, it can have a very aggressive clinical and imaging presentation overlapping with infectious osteomyelitis and malignancy. Therefore, radiologists and clinicians need to be aware of its clinical and imaging presentation to avoid morbidity associated with more aggressive treatment. We present the case of a ten-year-old female with CRMO as a solitary expansile-mixed lytic and sclerotic lesion in the distal femoral diaphysis. The diaphyseal location and mixed lytic and sclerotic appearance are less common and have an aggressive imaging appearance. We also review the pathophysiology, imaging findings, and therapeutic approach to this uncommon but clinically important condition.